Robust estimation of interconnected systems subject to sensornonlinearities - Mahmoud, Magdi S; AL-Sunni, Fouad M (Optimal control applications & methods, 2013)
SUMMARY An efficient robust LMI-based scheme is developed for decentralized state-estimation of linear interconnected systems with static nonlinear interconnections and subjected to sensor nonlinearities. The interconnections satisfy quadratic constraints with manipulated parameters and the sensor nonlinearities are modeled as sector nonlinearities. The design procedure utilizes a general linear estimator structure and consists of two steps: the first giving a block-diagonal Lyapunov matrix together with the robustness degree and the second determining the filter parameters. A numerical example is provided to illustrate the applicability of the method. Copyright © 2012 John Wiley & Sons, Ltd. [PUBLICATION ABSTRACT]